A new mechanism for reduced sensitivity to demethylation‐inhibitor fungicides in the fungal banana black Sigatoka pathogen Pseudocercospora fijiensis. (13th February 2018) - Diaz‐Trujillo, Caucasella; Chong, Pablo; Stergiopoulos, Ioannis; Cordovez, Viviane; Guzman, Mauricio; De Wit, Pierre J. G. M.; Meijer, Harold J. G.; Scalliet, Gabriel; Sierotzki, Helge; Lilia Peralta, Esther; Arango Isaza, Rafael E.; Kema, Gerrit H. J.
Summary: The Dothideomycete Pseudocercospora fijiensis, previously Mycosphaerella fijiensis, is the causal agent of black Sigatoka, one of the most destructive diseases of bananas and plantains. Disease management depends on fungicide applications, with a major contribution from sterol demethylation‐inhibitors (DMIs). The continued use of DMIs places considerable selection pressure on natural P. fijiensis populations, enabling the selection of novel genotypes with reduced sensitivity. The hitherto explanatory mechanism for this reduced sensitivity was the presence of non‐synonymous point mutations in the target gene Pfcyp51, encoding the sterol 14α‐demethylase enzyme. Here, we demonstrate a second mechanism involved in DMI sensitivity of P. fijiensis . We identified a 19‐bp element in the wild‐type (wt) Pfcyp51 promoter that concatenates in strains with reduced DMI sensitivity. A polymerase chain reaction (PCR) assay identified up to six Pfcyp51 promoter repeats in four field populations of P. fijiensis in Costa Rica. We used transformation experiments to swap the wt promoter of a sensitive field isolate with a promoter from a strain with reduced DMI sensitivity that comprised multiple insertions. Comparative in vivo phenotyping showed a functional and proportional up‐regulation of Pfcyp51, which consequently decreased DMI sensitivity. Our data demonstrate that point mutations in the Pfcyp51 coding domain, as well as promoter inserts, contribute to the reduced DMI sensitivity of P. fijiensis . These results provide new insights into the importance of the appropriate use of DMIs and the need for the discovery of new molecules for black Sigatoka management.